2022
DOI: 10.1136/bmjopen-2021-051775
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers’ perceptions and attitudes towards the UK’s COVID-19 vaccination programme: a rapid qualitative appraisal

Abstract: ObjectivesWhile there is research relating to perceptions of vaccines among healthcare workers (HCWs), the evidence base in relation to COVID-19 remains limited. The aim of this study was to explore HCWs’ perceptions and attitudes towards vaccines and the COVID-19 vaccination programme in the UK, including their expectations and views on promoting vaccination to others.DesignThis study was designed as a rapid qualitative appraisal, integrating data from a review of UK policies and guidance on COVID-19 vaccinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
(68 reference statements)
6
19
0
1
Order By: Relevance
“…The safety issue of vaccine along with historical perceptions of childhood vaccinations such as polio, propagated by misinformation through the social media may have had an impact on early acceptance of vaccines in our study participants. Similar findings were also reported in a qualitative study in UK [17], where misinformation about the Covid-19 vaccine impacted HCWs' attitude towards Covid-19 vaccination.…”
supporting
confidence: 86%
“…The safety issue of vaccine along with historical perceptions of childhood vaccinations such as polio, propagated by misinformation through the social media may have had an impact on early acceptance of vaccines in our study participants. Similar findings were also reported in a qualitative study in UK [17], where misinformation about the Covid-19 vaccine impacted HCWs' attitude towards Covid-19 vaccination.…”
supporting
confidence: 86%
“…This risk, that confusion will fuel vaccine hesitancy, means that policymakers must scrutinize COVID-19 vaccine policy updates and communication strategies to optimize message consistency and explain with candor and empathy the actions being taken to reduce uncertainty (23). Clarity around the rationale for policy change was felt to be needed by HCP too, a nding that resonates with other studies that have similarly demonstrated policy in uences clinical practice, HCP wellbeing and patient trust (24,25). Their perception was public trust in them as HCP, and COVID-19 vaccines was eroded by constantly tweaked recommendations and the lack of clarity about when new policy directives could be implemented.…”
Section: Discussionmentioning
confidence: 90%
“…Frontline healthcare providers gave stark commentaries about the emotional burden of delivering vaccination programs in busy environments where increasingly complicated and constantly changing policy became an additional stressor rather than a lever to enact equitable vaccine provision. How HCP experience policy changes is an essential point because of their pivotal role in in uencing patients' vaccination choices (25,32,33). Individuals involved in the on-the-ground vaccine rollout need time to understand to changes, translate and adapt operations, and adjust communication-all before facing patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, conducting our study before the introduction of mandatory vaccination for HCWs certainly allowed for better identification of the determinants of vaccination intention. To our knowledge, few qualitative studies have contributed to the identification of the determinants of vaccination intention in the context of the COVID-19 pandemic among a key population such as HCWs [ 64 , 65 ]. Our study highlights the influence of the global environment on vaccination intention and underlines the need to implement systemic measures adapted to local specificities.…”
Section: Discussionmentioning
confidence: 99%